1990
DOI: 10.1007/bf01344288
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in lipid class and fatty acid composition of two small copepods in Balsfjorden, northern Norway

Abstract: Abstract. Zooplankton were collected at Svartnes, northern Norway between 1985 and 1986. The lipid class and fatty acid composition of a subarctic population of Pseudocalanus acuspes (Giesbrecht, 1881) and Acartia longiremis Lilljeborg are described for four seasons of the year. The results are discussed in relation to the seasonal variation in abundance and dry weight of the predominant developmental stages. The lipid composition of these small copepod species resembles that of omnivorous or carnivorous spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1
1

Year Published

1990
1990
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(42 citation statements)
references
References 28 publications
3
37
1
1
Order By: Relevance
“…The percentages of PUFA, such as EPA and DHA, in fish muscle are dependent on diet (Sargent 1997). Variations in fatty acid composition might be related to the changes in nutritional habits of the fish (Norrobin et al 1990). Other factors such as the size or age, reproductive status, geographic location, season, and temperature may influence the fatty acid composition of the fish muscle (Leger et al 1977;Alasalvar et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The percentages of PUFA, such as EPA and DHA, in fish muscle are dependent on diet (Sargent 1997). Variations in fatty acid composition might be related to the changes in nutritional habits of the fish (Norrobin et al 1990). Other factors such as the size or age, reproductive status, geographic location, season, and temperature may influence the fatty acid composition of the fish muscle (Leger et al 1977;Alasalvar et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…was also observed in the White Sea (Pertsova 1981). Norrbin (Norrbin et al 1990;Norrbin 1996) suggested that it is less a continuous process, triggered by the physiological state as proposed by McLaren et al (1989), but rather a speciWc switching date, at which P. acuspes copepodids stop maturation but proceed to accumulate lipids. Klein Breteler and Gonzalez (1988) suspected that changes to poor food conditions are necessary to induce hormonal cessation of development in favor of lipid production.…”
Section: Onset Of Overwinteringmentioning
confidence: 99%
“…in Arctic regions (e.g. Pertsova 1981;McLaren et al 1989;Norrbin et al 1990;Norrbin 1991;Conover and Siferd 1993), with highest reproductive activities in spring, a successive accumulation of resting copepodite stages starting in early summer and a potential interposition of minor summer generations. This is supported by the corresponding lipid-storing strategies of P. acuspes.…”
Section: Onset Of Overwinteringmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to ingest small-sized food particles could be an important advantage over large copepods, and perhaps a reason for the overwhelming numerical abundance of D. forcipatus in some areas of the southern Patagonian shelf. Opportunistic feeding must be a supplement to energy storage for smaller copepod species occurring at high latitudes because of their higher metabolic rates and the limitation of storage space (NORRBIN et al, 1990). Grazing during a previous temporal window may explain that higher abundances of nearly all copepodite stages appeared to be related to low concentrations of most potential food items.…”
Section: Drepanopus Forcipatusmentioning
confidence: 99%